KEGIATAN MENGISI POLA DENGAN KERTAS ORIGAMI UNTUK MENINGKATKAN KREATIVITAS ANAK TK PELITA KECAMATAN KOTO BARU KABUPATEN DHARMASRAYA - Yeni Susanti; Lesis Andre; B.R.E Yunanda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study addresses the problem of underdeveloped creativity in early childhood and thelack of appropriate activities to enhance it. The purpose is to improve the creativity of earlychildhood children through pattern filling activities using origami paper pieces. The researchwas conducted as a qualitative descriptive study at Pelita Kindergarten, Koto Baru District,Dharmasraya Regency, from April 14 to 17, 2025. Data sources included the principal,group B class teachers, and 15 students. Data were collected through observation,interviews, and documentation. Analysis involved data reduction, data display, drawingconclusions, and verification, with data validity ensured by triangulation.The findings showthat pattern filling activities with origami paper were implemented according to establishedprocedures. Initially, 73% of children’s creativity was undeveloped. However, after theintervention, creativity improved significantly across five indicators. For Fluency (IdeaFluency), 14 out of 15 children (93%) excelled in creating ideas. For Flexibility, the highestsub-indicator was the ability to determine techniques, also at 93% with 14 children.Originality (Authenticity) showed creative ideas at 73% with 11 children. Elaborational(Detailedness) reached 100% accuracy with all 15 children. Sensitivity was demonstratedby 14 children (93%) responding effectively to their own problems. These results confirmthat pattern filling with origami paper is an effective activity to enhance early childhoodcreativity, fostering idea generation, flexibility, originality, elaboration, and sensitivity.